2020
DOI: 10.1200/jco.19.01538
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Functional Outcomes After Hypofractionated or Conventionally Fractionated Radiation for Prostate Cancer: A National Cohort Study in England

Abstract: PURPOSE The aim of the current study was to determine patient-reported functional outcomes in men with prostate cancer (PCa) undergoing moderately hypofractionated (H-RT) or conventionally fractionated radiation therapy (C-RT) in a national cohort study. PATIENDS AND METHODS All men diagnosed with PCa between April 2014 and September 2016 in the English National Health Service undergoing C-RT or H-RT were identified in the National Prostate Cancer Audit and mailed a questionnaire at least 18 months after diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…These real-world results are in keeping with the Conventional or Hypofractionated High Dose Intensity Modulated Radiotherapy in Prostate Cancer (CHHiP) and Radiation Therapy Oncology Group 0415 studies that found no clinically meaningful differences in PROs between HRT and CRT. 18 , 19 The proportion of men reporting moderate or big urinary or bowel bother was less than 10% and was consistent with the CHHip study. 20 A national cohort study from England 18 also reported no differences in EPIC-26 urinary and bowel function between men receiving HRT or CRT, with mean scores in the order of 86 across the domains and consistent with the findings in this cohort study.…”
Section: Discussionsupporting
confidence: 80%
“…These real-world results are in keeping with the Conventional or Hypofractionated High Dose Intensity Modulated Radiotherapy in Prostate Cancer (CHHiP) and Radiation Therapy Oncology Group 0415 studies that found no clinically meaningful differences in PROs between HRT and CRT. 18 , 19 The proportion of men reporting moderate or big urinary or bowel bother was less than 10% and was consistent with the CHHip study. 20 A national cohort study from England 18 also reported no differences in EPIC-26 urinary and bowel function between men receiving HRT or CRT, with mean scores in the order of 86 across the domains and consistent with the findings in this cohort study.…”
Section: Discussionsupporting
confidence: 80%
“…In future, the validated Spanish EPIC-16 could be utilized in a larger-scale analysis with more longitudinal components to further assess PROs comparing different types of radiation therapies, similar to what has been recently done for EPIC-26 by Nossiter, et al [ 23 ].…”
Section: Discussionmentioning
confidence: 91%
“…Reducing the number of radiotherapy fractions, but achieving the same health outcomes across the life cycle, would be a high value intervention given the reduction in resource costs of treatment delivery and in treatment burden with potential quicker return to previous activities. Furthermore, some hypofractionated treatments may result in reduced toxicities, which over the cancer care cycle is likely to decrease healthcare and societal costs by lower need for interventions to manage these complications, or to enable individuals to partake in work and day to day activities [23,24].…”
Section: Value-based Healthcare a Radiotherapy Perspectivementioning
confidence: 99%